2018
DOI: 10.1007/s10802-018-0480-0
|View full text |Cite
|
Sign up to set email alerts
|

Children Sleep and Antisocial Behavior: Differential Association of Sleep with Aggression and Rule-Breaking

Abstract: There is a strong relationship between sleep and behavioral problems. These findings are often interpreted via environmental explanations, such that poor sleep directly exacerbates or causes symptoms of aggression and behavior problems. However, there are other possible explanations, such that the genes predicting poor sleep also predict aggression or rule-breaking. The current study sought to elucidate the origin of this relationship. The sample was composed of 1,030 twin pairs (426 monozygotic and 604 dizygo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 50 publications
0
16
0
1
Order By: Relevance
“…Shakoor et al [ 41 ] repeated these analyses in a smaller sample from the same study ( N = 7,442) and found that the heritability for insomnia was lower for boys (34%) than girls (42%). Madrid-Valero et al [ 42 ] also found that the heritability for Child Behaviour Checklist (CBCL) items “sleeps less than most kids” and “trouble sleeping” was 85% and 62%, respectively, in 2,060 children (age 8.06 years, range = 6–12). Other twin studies have examined the heritability of sleep onset latency (SOL), which in cases might be relevant to sleep onset insomnia.…”
Section: Heritability Of Sleep and Sleep Disorders In Childhood And Adolescencementioning
confidence: 99%
“…Shakoor et al [ 41 ] repeated these analyses in a smaller sample from the same study ( N = 7,442) and found that the heritability for insomnia was lower for boys (34%) than girls (42%). Madrid-Valero et al [ 42 ] also found that the heritability for Child Behaviour Checklist (CBCL) items “sleeps less than most kids” and “trouble sleeping” was 85% and 62%, respectively, in 2,060 children (age 8.06 years, range = 6–12). Other twin studies have examined the heritability of sleep onset latency (SOL), which in cases might be relevant to sleep onset insomnia.…”
Section: Heritability Of Sleep and Sleep Disorders In Childhood And Adolescencementioning
confidence: 99%
“…In another twin study of children aged between 6 and 12 years, the relationship between different measures of sleep and two dimensions of antisocial behavior was studied (Madrid-Valero, Ordoñana, Klump, & Burt, 2019). A strong association between sleep measures and both dimensions of antisocial behavior was found.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…The systematic review also highlighted that genetic factors play a role in the association between these sleep variables and a wide variety of other variables relevant for general health. Twin studies have demonstrated that there is a substantial genetic overlap between sleep quality/duration/ sleep disorders and depression (Gasperi et al, 2017;Gehrman et al, 2011;Gregory et al, 2011;Lind et al, 2017), anxiety (Gehrman et al, 2011;Gregory et al, 2011), psychotic-like experiences (Taylor et al, 2015), neuroticism (Butkovic et al, 2014), externalising behaviors (Barclay et al, 2011;Madrid-Valero et al, 2019) and pain (Gasperi et al, 2017;Pinheiro et al, 2018) among other variables relevant for health. These results are largely consistent across the behavioral genetic literature and point to a significant genetic correlation between sleep disturbances and different disorders or diseases.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Aunado a la amabilidad y consideración, el buen trato autogenerado físico también se presentó como un predictor negativo de la agresividad física. De acuerdo con diversos autores, conductas relacionadas con el buen trato autogenerado físico, como hacer ejercicio, cuidar la alimentación y el descanso, se asocian con una reducción de la agresividad en diversas etapas vitales (Madrid-Valero, Ordoñana, Klump, & Burt, 2019;Park, Chiu, & Won, 2017;Zahedi et al, 2014). Por su parte, Martínez y González (2017) relacionan actividades como practicar ejercicio con un mejor autoconcepto físico y ajuste social en adolescentes, y un aumento de sus conductas prosociales.…”
Section: Discussionunclassified